An ideological response to combating terrorism - the Singapore perspective - Muhammad Haniff Hassan (2021)
The article examines alternative strategies to combating the scourge of terrorism beyond military approaches. There is now more realization, especially after the difficulties experienced in Iraq today, that an innovative multi-pronged mix of methods is needed to combat international terrorism. The paper looks at an ideological response towards combating terrorism by looking at the Singapore experience. The Singapore government recognizes the importance of an ideological response as an integral part of counterterrorism measures. Terrorism occurs when opportunity, motivation and capability meet. The prevention of terrorism requires the elimination of at least one of these three factors- motivation- often driven by ideology. The paper will look at direct and indirect initiatives undertaken in Singapore to combat terrorism and will also look at the Muslim community in Singapore's response to the threat to Singapore society. Lastly, the article will examine some lessons learnt from the Singapore experience in applying an ideological approach in combating terrorism as well as some recommendations of what more can be done to move forward. © Taylor & Francis.